ຜົນກະທົບຂອງເຂື່ອນໄຟຟ້າຕໍ່ ການປະມົງໃນແມ່ນ້ຳຂອງ - Geheb, Kim; Pukinskis, Ilse (CGIAR Challenge Program on Water and Food, 2012)
Reviews Mekong fishery basics, fish migrations, habitats, biodiversity, aquaculture production and reservoir fisheries.